Bibliometrics and Visual Analysis of Adult-onset Still Disease (1976–2020) - Xu, Bowen; Wang, Jian; Meng, Xiaoying; Bao, Binghao (Frontiers in Public Health, 2022)
Background Adult-onset Still Disease (AoSD) is a rare disorder without standardized diagnostic criteria. People are paying more and more attention to its research. At present, no published studies have assessed the AoSD field using bibliometric tools. This study aimed to analyze research hotspots and frontiers through bibliometrics to provide a scientific and accurate reference for new and existing researchers. Methods Data were obtained from the Web of Science core database and analyzed by CiteSpace, VOSviewer, and Microsoft Excel. Results Involving 86 countries and regions, a total of 11,121 authors published 2,199 articles in 676 journals. These studies were published from 1976 to 2020. The United States published the most related articles (397). The United States, France, Italy, and Germany were the top four countries with a high H-index. Authors and institutions with high number of published articles and high citations are mainly located in France and Italy. High-frequency keywords include classification, criteria, diagnosis, and therapy method. Keyword clustering covers the connection between AoSD and rheumatoid arthritis, disease diagnosis, classification, and risk factors. Conclusions The research on AoSD focuses on the diagnosis and differential diagnosis of the disease. Targeted therapy will become a research hotspot in the future, and relevant clinical research needs to appropriately expand the sample size and improve the credibility of the conclusions. The data reported in this study can serve as a useful resource for researchers studying AoSD.